2019
DOI: 10.2478/orhu-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Cases of occasional interspecific brood parasitism and egg dumping in Hungary

Abstract: There are numerous publications in the ornithological literature on mixed-species broods, i.e. on cases when a species lays some or all of its eggs into the nests of other species. This phenomenon, known as brood parasitism, has not yet been studied in Hungary. Here, I use the term brood parasitism, but I could not separate cases of egg dumping, a reproductive error by females. Based on literature and my own observations, I found evidence for interspecific brood parasitism in 28 species breeding in Hungary, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…As long as interspecific brood parasitism was frequently described in Gruiformes (Rallidae) (Forman 2003, Haraszthy 2019b, the phenomenon has rarely been observed within Charadriiformes (Amat 1998, Yom-Tov 2001, Niemczynowicz et al 2015. In this context, these observations are important and can be important points in the understanding of the occurrence and evolution of brood parasitism in birds.…”
Section: Referencesmentioning
confidence: 97%
“…As long as interspecific brood parasitism was frequently described in Gruiformes (Rallidae) (Forman 2003, Haraszthy 2019b, the phenomenon has rarely been observed within Charadriiformes (Amat 1998, Yom-Tov 2001, Niemczynowicz et al 2015. In this context, these observations are important and can be important points in the understanding of the occurrence and evolution of brood parasitism in birds.…”
Section: Referencesmentioning
confidence: 97%
“…Reports published to date include mixed clutches of great tits with blue tits (Busse and Gotzman, 1962;Baucells, 1990;Petrassi et al, 1998;Barrientos et al, 2015), Eurasian nuthatches (Sitta europaea) (Dolenec, 2002;Haraszthy, 2019), pied flycatchers (Ficedula hypoleuca) (Busse and Gotzman, 1962), wrynecks (Jynx torquilla) (Busse and Gotzman, 1962), redstarts (Phoenicurus phoenicurus) (Shy, 1982), varied tits (Sittiparus varius) (Suzuki and Tsuchiya, 2010), common starlings (Sturnus vulgaris) (Busse and Gotzman, 1962), European robins (Erithacus rubecula) (Lack, 1953) and Eurasian tree sparrows (Passer montanus) (Busse and Gotzman, 1962). Mixed clutches have also been reported between other species (Busse and Gotzman, 1962;Merilä, 1994;Samplonius and Both, 2014;Haraszthy, 2019;Garrido-Bautista et al, 2022). It has been suggested that great tits might even be parasitized by common cuckoos (Cuculus canorus) and raise both their own nestlings and the cuckoo nestlings (Grim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the Eurasian tree sparrow (Passer montanus), Busse and Gotzman (1962) cited several cases in which these sparrows hosted great tit eggs among their own, but not vice versa. The closest thing to a European tree sparrow ('sparrow' hereafter) egg ending up among a great tit clutch is the case described by Haraszthy (2019), in which a sparrow egg remained in the nest box after its siblings fledged. This nest box was later occupied by great tits and the sparrow egg remained there along with the great tit clutch, but it never hatched.…”
Section: Introductionmentioning
confidence: 99%